Retention of Nutritional Quality of Solar Dried Carrot (Daucus carota L.) During Storage (Bangladesh Journal of Scientific and Industrial Research, 2011)
Carrot (Daucus carota L.) is a root crop. It belongs to the umbelliferae family. Carrot contains the highest amount of carotene among all the fruits and vegetables which the body converts to vitamin-A. Carrot was dried in a solar drier and packed in polyethylene bags, heat sealed and kept in tin container at ambient temperature for 8 (eight) months. Moisture, reducing sugar, total sugar, starch, protein, fat, vitamin-C, ß-carotene content, energy value and reconstitution time of the product were analysed during its storage period at the interval of 2 months. The initial nutrient of fresh carrot and solar dried carrot for the above parameters were analysed. During the storage period protein, starch and total sugar content decreased slightly, vitamin-C decreased remarkably, â-carotene content decreased very slowly and moisture content increased gradually. Sensory properties such as appearance, colour, flavour, texture, taste and physical parameters such as over-all shrinkage ratio, drying ratio, rehydration ratio of the product were also assessed. By assessing all the parameters it is revealed that the product is acceptable for 6 (Six) months. Key words: Carrot; Solar drying; Storage behaviour; Physical parameters; Nutrients DOI: 10.3329/bjsir.v45i4.7381 Bangladesh J. Sci. Ind. Res. 45(4), 359-362, 2010